Corrosions of citizenship: contradctions of national ideology on the present phase of internationalization of capitalism - Rodrigues de Almeida, Lúcio Flávio (Pontifícia Universidade Católica de São Paulo, 2004)
This article focuses on some political and ideological impacts produced by the present phase of uneven internationalization of social capitalist relations. The alterations to the roles of the State and the correlated crisis of citizenship and national ideology are studied in order to examine the emergent social struggles.